Crosslinked chitosan membranes for pervaporation separation of isopropanol-water mixtures - Hassan, H. (Faculty of Chemical and Natural Resource Engineering, UTM, 2008)
Pervaporation, a membrane process for separating liquid organic mixtures has been regarded as an energy efficient alternative to conventional separation methods especially when involves the separation beyond the azeotropic point. In the present study, pervaporation membranes were developed from chitosan obtained from chitin using the available shrimp shells. Membranes prepared from chitosan were crosslinked with aluminum nitrate solution. The performances of the membranes were investigated in terms of its permeation flux and separation factor in the separation of isopropanol-water mixtures. The crosslinked chitosan membranes showed better performance than that of the uncrosslinked chitosan membranes at high isopropanol in feed composition showing that chitosan membranes has the potential to be used for the dehydration of isopropanol especially at high isopropanol composition in feed mixtures.